The impact of lithologic heterogeneity and focused fluid flow upon gas hydrate distribution in marine sediments. Issue 9 (2nd September 2014) - Chatterjee, Sayantan; Bhatnagar, Gaurav; Dugan, Brandon; Dickens, Gerald R.; Chapman, Walter G.; Hirasaki, George J.
Abstract Gas hydrate and free gas accumulation in heterogeneous marine sediment is simulated using a two‐dimensional (2‐D) numerical model that accounts for mass transfer over geological timescales. The model extends a previously documented one‐dimensional (1‐D) model such that lateral variations in permeability (k) become important. Various simulations quantitatively demonstrate how focused fluid flow through high‐permeability zones affects local hydrate accumulation and saturation. Simulations that approximate a vertical fracture network isolated in a lower permeability shale (kfracture >> kshale) show that focused fluid flow through the gas hydrate stability zone (GHSZ) produces higher saturations of gas hydrate (25–70%) and free gas (30–60%) within the fracture network compared to surrounding shale. Simulations with a dipping, high‐permeability sand layer also result in elevated saturations of gas hydrate (60%) and free gas (40%) within the sand because of focused fluid flow through the GHSZ. Increased fluid flux, a deep methane source, or both together increase the effect of flow focusing upon hydrate and free gas distribution and enhance hydrate and free gas concentrations along the high‐permeability zones. Permeability anisotropy, with a vertical to horizontal permeability ratio on the order of 10−2, enhances transport of methane‐charged fluid to high‐permeability conduits. As a result, gas hydrate concentrations are enhanced within these high‐permeability zones. The dip angle of these high‐permeability structures affects hydrate distribution because the vertical component of fluid flux dominates focusing effects. Hydrate and free gas saturations can be characterized by a local Peclet number (localized, vertical, focused, and advective flux relative to diffusion) relative to the methane solubility gradient, somewhat analogous to such characterization in 1‐D systems. Even in lithologically complex systems, local hydrate and free gas saturations might be characterized by basic parameters (local flux and diffusivity).